2020
DOI: 10.1007/s12311-020-01172-0
|View full text |Cite
|
Sign up to set email alerts
|

Cathodal Cerebellar tDCS Combined with Visual Feedback Improves Balance Control

Abstract: Balance control is essential to maintain a stable body position and to prevent falls. The aim of this study was to determine whether balance control could be improved by using cerebellar transcranial direct current stimulation (tDCS) and visual feedback in a combined approach. A total of 90 healthy volunteers were randomly assigned to six groups defined by the delivery of tDCS (cathodal or anodal or sham) and the provision or not of visual feedback on balance during the acquisition phase. tDCS was delivered ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Neuronal excitability changes induced by tDCS are supposed to be mediated by processes which are similar to long-term potentiation (LTP) and depression (LTD), among others [ 45 ]. These neurobiological mechanisms could significantly favor the intermodal recalibration induced by our initial protocol [ 35 , 46 ]. Interestingly, neurobiological post-effects can be observed during minutes and up to several hours after the end of tDCS stimulation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal excitability changes induced by tDCS are supposed to be mediated by processes which are similar to long-term potentiation (LTP) and depression (LTD), among others [ 45 ]. These neurobiological mechanisms could significantly favor the intermodal recalibration induced by our initial protocol [ 35 , 46 ]. Interestingly, neurobiological post-effects can be observed during minutes and up to several hours after the end of tDCS stimulation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, while atDCS expedites the adaptation process, it may not be beneficial for gait and balance measures obtained after the training session. In a more recent study, cathodal tDCS to the cerebellum was demonstrated to improve balance [ 48 ]. At rest, the cerebellum typically exerts an overall inhibitory tone on the primary cortex, in a phenomenon known as cerebellar brain inhibition (CBI) [ 49 ], that is reduced after motor learning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cathodal stimulation typically results in a reduced CBI which influences motor learning. Therefore, one could hypothesize that cathodal rather than anodal polarity may induce positive changes in gait [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many studies combining NIBS with fMRI or EEG [ 212 ] techniques, for example, TMS-EEG, and TMS-fMRI can be used in combination to better individualize and synchronize neuromodulation in stroke patients, revealing possible remote top-down effects at the neural population level [ 113 ]. Furthermore, the combination of cathodal cerebellar tDCS and visual feedback was reported to improve balance control in a healthy population [ 217 ] and these findings should also be considered to deeply elaborate the mechanism of NIBS techniques in post-stroke dysfunction, which will be a future direction of development.…”
Section: Current Status and Prospectsmentioning
confidence: 99%